Interpretation of the Meaningfulness on Ecomathrigi Learning Model - Adun Priyanto (International Journal of Educational Development, 2024)
Meaningful learning is analyzed through the interaction between learning subjects and the episteme framework of education. This research is to determine the interpretive activities of causality of the relationship between 3 (three) dimensions of the subject phenomenological analysis model (ethnographic context of learning) and determine the influence of the meaningful process of interaction between learning subjects. So that this approach model uses several observations of semiotic analysis variables, gestures, and interpersonal relationships. It also seeks to translate between interactions, semiotic resources, and meaning-making. Analysis using the theory of Meaningful Learning Ausubel model learning at Islamic Junior High School Al-Azhar 15 in Cilacap. To determine the meaningfulness of the interaction of learning the Mathematics Ecomathrigi model, data collection techniques use observation, documentation, and interviews. The results are there was a significant mutual influence between students-teachers-artifacts in the meaningfulness of mathematics learning; The significant influence is also due to the use of the Ecomathrigi model learning approach in building learning interaction; The consequences of the significant influence of cognitive structure on new students on alumni perspectives on mathematics learning, teachers and schools.